Visualization of information in ski jumping and its utilization - Yamamoto, K.; Tsubokura, M.; Matsuzawa, M.; Mori, S.; Miyamoto, N. (Journal of Visualization Society of Japan, 2020)
In biomechanics research on ski jumping, a series of movements are analyzed by classifying them into six phases: approach, take-off, early flight, stable flight, landing preparation and landing. It is a well-known fact that movement from the take-off to the flight is important for improving performance. In actual competition, the athlete's downhill and flight speed reaches about 90 km/h, so aerodynamics dominates the competition performance. As many previous studies have shown, there is no doubt that aerodynamic forces acting on ski jumpers and skis have a significant effect on competitive performance. In studies aimed at improving athletic ability, there are many reports from the viewpoint of aerodynamics and biomechanics, and visualization of the obtained knowledge and information is required. This paper introduces recent research trends and measurement techniques. Then, the outline of the utilization of this visualized information in the training and competition field is described.